2012
DOI: 10.1160/th11-12-0875
|View full text |Cite
|
Sign up to set email alerts
|

Deficiencies of antithrombin, protein C and protein S – Practical experience in genetic analysis of a large patient cohort

Abstract: Deficiencies of natural anticoagulant proteins including antithrombin (AT), protein C (PC) and protein S (PS) are important causes of inherited thrombophilia. This study aimed to report on the practical experience gained in performing genetic analyses of a large cohort of patients with AT, PC and PS deficiencies and to relate this knowledge to clinical application. We genotyped a large cohort of 709 unrelated patients with AT (231), PC (234) and PS (244) deficiencies referred to us by physicians throughout Ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
77
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 38 publications
11
77
3
2
Order By: Relevance
“…This is in contrast to a study by Caspers et al, 16 conducted in German patients, in whom the mutation detection rate remained at a level of about 70% for AT activities up to 75%. 16 It seems that in our population, a genetic analysis of the SERPIC1 gene should be performed in patients Mutations were given coordinates according to the HUGO recommendations for mutation nomenclature (http://www.hgvs.org).…”
contrasting
confidence: 97%
See 2 more Smart Citations
“…This is in contrast to a study by Caspers et al, 16 conducted in German patients, in whom the mutation detection rate remained at a level of about 70% for AT activities up to 75%. 16 It seems that in our population, a genetic analysis of the SERPIC1 gene should be performed in patients Mutations were given coordinates according to the HUGO recommendations for mutation nomenclature (http://www.hgvs.org).…”
contrasting
confidence: 97%
“…On the other hand, the study on the German population showed that the genetic analysis of the PROC gene should be performed in patients with PC activities below 70%, which worked fine also for our patients. 16 Similarly, in our PS -deficient patients, no mutations were detected above 53% of PS activity, which is in line with the study by Caspers et al 16 The major study limitation was a relatively small sample size; however, we analyzed all eligible patients suspected of these types of thrombophilia in our center. For the new mutations, functional studies should be performed in addition to in silico predictions to prove their detrimental effect.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The overall mutation detection rate (3 genes combined) and the order were similar to those recently reported in a large cohort of patients from Germany (overall 65.8%, with SERPINC1 84%, PROC 69.2%, and PROS1 43.2%). 46 The overall mutation detection rate in the population group in our study was lower than that in the group of patients (36.7% versus 56.7%), but higher than the 15.8% in a population study in China recently reported by Zhu et al 16 In addition, the results from the study by Zhu et al demonstrated the highest mutation detection rate in PROC (31.3%), followed by SERPINC1 (9.7%) and PROS1 (6.3%). This striking difference was in part due to the presence of two prevalent missense mutations (Arg79Cys and Ser148Pro) in the Korean population.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Recent advances in the intensive cares, cardiac surgery, and transplantation medicine along with the imaging diagnosis may contribute to the increased number of pediatric patients with thrombosis (2,3). The established genetic risks of venous thromboembolism (VTE) include protein C (PC), protein S (PS), and antithrombin (AT) deficiency, as well as factor V G1691A (FVL) and prothrombin G20210A (FII) variants (4). The high incidence of VTE in Caucasians (5) is explained by the fact that FVL and FII G20210A carriers were found in 20-60% of adult VTE patients in Caucasian but not Asian ancestries (6)(7)(8)(9).…”
mentioning
confidence: 99%